The Influence of the Size Effects on the Termoelectrical Properties of PbTe Thin Films - M.A. Ruvinskii; O.B. Kostyuk; B.S. Dzundza (Журнал нано- та електронної фізики)
Based on kinetic Boltzmann equation the boundary problem of calculating the conductivity and Seebeck coefficient for a film with a rectangular cross section is solved. Mirror-diffuse mechanism of reflection of the charge carriers from the surfaces of the film is considered. Calculations were performed for different thicknesses semiconductor n-PbTe. Based on the model of quantum flat rectangular and with infinitely high walls pit, the value of Seebeck coefficient S was calculated for n-PbTe. The quantum and classical size effects were experimentally investigated. The transition from the oscillating to monotonic dependences of the thermoelectric parameters of nanostructures based on n-PbTe has been proved.